PENGUJIAN KUALITAS INFORMASI DAN ASIMETRI INFORMASI SEBELUM DAN SETELAH ADOPSI IFRS DI UNI EROPA - Dwianto Mukhtar Latif (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aims to provide empirical evidence related to the influence of mandatory IFRS adoption on the information quality and information asymmetry. This research is an extension of the research Armstrong et al. (2010) about the positive reaction to the mandatory IFRS adoption process in the European Market associated with the perception that IFRS will improve the information quality and reduces information asymmetry. By using secondary data as many as 426 manufacturing firms obtained from the OSIRIS database includes data published financial statements and stock prices, this research compared the information quality and information asymmetry between prior period (2002-2004) and period after the IFRS adoption. The results provide that an increase in the information quality after the mandatory IFRS adoption in the EU. However, improving the information quality is not followed by a decrease in information asymmetry such as Ball’s (2006) opinion, and the results of this study showed that an increase in information asymmetry after mandatory IFRS adoption in the EU. As Hung and Subramanyam (2007) states that the accounting standards is not a major factor that can affect the quality of accounting information.